2016
DOI: 10.4103/1735-1995.183997
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions involved in swallowing: Evidence from stroke patients in a cross-sectional study

Abstract: Background:Limited data available about the mechanisms of dysphagia and areas involving swallow after brain damage; accordingly it is hard to predict which cases are more likely to develop swallowing dysfunction based on the neuroimaging. The aim of this study was to investigate the relationship between brain lesions and dysphagia in a sample of acute conscious stroke patients.Materials and Methods:In a cross-sectional study, 113 acute conscious stroke patients (69 male mean [standard deviation (SD)] age 64.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Our data show that dysphagia can occur in ischaemic cerebellar stroke with a prevalence of about 13%. To date, conflicting data exist about whether lesions only in the cerebellum could in general lead to post-stroke dysphagia [5][6][7][8][9]. Reasons for hitherto inconclusive results might be related to patient selection and number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that dysphagia can occur in ischaemic cerebellar stroke with a prevalence of about 13%. To date, conflicting data exist about whether lesions only in the cerebellum could in general lead to post-stroke dysphagia [5][6][7][8][9]. Reasons for hitherto inconclusive results might be related to patient selection and number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In normal subjects, Babaei et al ( 2013 ) and Malandraki et al ( 2009 ) used brain fMRI to demonstrate increased activation in the cingulate, insula, sensorimotor cortex, prefrontal and parietal cortices, cerebellum, and thalamus during swallowing. Furthermore, Vahdat et al ( 2011 ) observed that alterations in the functional connectivity of the sensorimotor network may be related to motor learning and the importance of the role of somatosensory region in swallowing had been gradually discovered (Babaei et al, 2013 ; Dehaghani et al, 2016 ; Mihai et al, 2016 ). In the present study, stroke patients received a variety of treatments to improve their swallowing, including motor functional training, thermal stimulation, postural compensation, oropharyngeal exercise, compensatory techniques, and swallowing maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used clinical observations, EEG, magnetoencephalography (MEG) or transcranial magnetic stimulation (TMS) to explore the cerebral areas associated with swallowing dysfunction (Robbins et al, 1993 ; Hamdy et al, 1997 ; Luan et al, 2013 ; Jestrovic et al, 2016 ). However, over recent years, functional magnetic resonance imaging (fMRI) has become a more popular tool with which to evaluate cerebral cortical function during volitional and reflexive swallowing in humans (Hamdy et al, 1999 ; Mosier K. et al, 1999 ; Mosier K. M. et al, 1999 ; Kern et al, 2001 ; Martin et al, 2001 ; Malandraki et al, 2011 ; Dehaghani et al, 2016 ). Li et al used fMRI to investigate cerebral cortical activation during swallowing with tasks in acute dysphagic stroke patients involving of unilateral hemisphere (Li et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for dysphagia include Older age, [6,7] Greater NIHSS, [6–11] Lower Barthel index, [12,13] Malnutrition or lower body mass index at admission, [12,14,15] Greater lesion volume, [10,11,16,17] Subcortical or cortical involvement, [18–20] Brainstem involvement, [9,18,19,21–24] Corticobulbar tract involvement, [13,25] White matter involvement, [9,13,25] Presence of dysarthria, [16,22] Presence of dysphonia or reduced maximum pitch, [16,26] and Cognitive impairment or dementia. [27,28]…”
Section: Introductionmentioning
confidence: 99%
“…The neural circuit that produces the swallowing pattern is located in the medulla oblongata. [5] Risk factors for dysphagia include Older age, [6,7] Greater NIHSS, [6][7][8][9][10][11] Lower Barthel index, [12,13] Malnutrition or lower body mass index at admission, [12,14,15] Greater lesion volume, [10,11,16,17] Subcortical or cortical involvement, [18][19][20] Brainstem involvement, [9,18,19,[21][22][23][24] Corticobulbar tract involvement, [13,25] White matter involvement, [9,13,25] Presence of dysarthria, [16,22] Presence of dysphonia or reduced maximum pitch, [16,26] and Cognitive impairment or dementia. [27,28] The consequences of dysphagia after a stroke include an increased risk of pulmonary complications, dehydration, malnutrition, and death.…”
Section: Introductionmentioning
confidence: 99%